Understanding the role of P2X7 in affective disorders—are glial cells the major players? - Stokes, Leanne; Spencer, Sarah J.; Jenkins, Trisha A. (Frontiers in Cellular Neuroscience, 2015)
The pathophysiology of several psychiatric disorders has been linked to biomarkers of inflammation generating a theory of major depressive disorder as an inflammatory disease and infection and autoimmunity as major risk factors for schizophrenia. The idea of pro-inflammatory cytokines altering behavior is now well accepted however many questions remain. Microglia can produce a plethora of inflammatory cytokines and these cells appear to be critical in the link between inflammatory changes and depressive disorders. Microglia play a known role in sickness behavior which has many components of depressive-like behavior such as social withdrawal, sleep alterations, and anorexia. Numerous candidate genes have been identified for psychiatric disorders in the last decade. Single nucleotide polymorphisms in the human P2X7 gene have been linked to bipolar disorder, depression, and to the severity of depressive symptoms. P2X7 is a ligand-gated cation channel expressed on microglia with lower levels found on astrocytes and on some neuronal populations. In microglia P2X7 is a major regulator of pro-inflammatory cytokines of the interleukin-1 family. Genetic deletion of P2X7 in mice is protective for depressive behavior in addition to inflammatory responses. P2X7-/- mice have been shown to demonstrate anti-depressive-like behavior in forced swim and tail suspension behavioral tests and stressor-induced behavioral responses were blunted. Both neurochemical (norepinephrine, serotonin, dopamine) and inflammatory changes have been observed in the brains of P2X7-/- mice. This review will discuss the recent evidence for involvement of P2X7 in the pathophysiology of depressive disorders and propose mechanisms by which altered signaling through this ion channel may affect the inflammatory state of the brain.